Diagnóstico turístico del casco urbano del municipio de Planeta Rica- Córdoba (2022)
The present work is focused on the tourist diagnosis of the urban area of the municipality of Planeta RicaCórdoba, which is of great importance, since this will allow determining the current state of tourism in the territory. The objective is to determine what is the main tourist typology in the territory, in order to reflect on the negative and positive aspects. I believe that it is important to carry out a tourism diagnosis in the territory since, in this area, studies have not yet been carried out in relation to tourism and it would serve as a basis for future research in relation to tourism. Therefore, to evaluate the current situation of tourism, a tourism inventory was carried out, applying the methodology of the Vice Ministry of Tourism to objectively evaluate the existing tourist attractions of the municipality. Likewise, in order to have a broader understanding of the current tourism situation in Planeta Rica, an analysis of tourism supply and demand was carried out, supported by authors such as Philip Kotler (tourism marketing) to investigate the behavior of the markets, how it is running tourist activity in travel agencies and hotels in terms of customer satisfaction. In the same way to know the perception and motivational part of tourists, investigating what motivates them to visit this place, what is their purchasing power, among other factors. With the results of this research, it is sought to generate long-term marketing strategies that allow a perennialization of tourism in Planeta Rica. Which this work would have a great contribution to society since it enriches the knowledge for possible studies of tourism in the municipality